Elevation of High-Mobility Group Protein Box-1 in Serum Correlates with Severity of Acute Intracerebral Hemorrhage. (14th September 2010) - Zhou, Yu; Xiong, Kun-Lin; Lin, Sen; Zhong, Qi; Lu, Feng-Lin; Liang, Hong; Li, Jing-Cheng; Wang, Jing-Zhou; Yang, Qing-Wu
Abstract : High-mobility group protein box-1 (HMGB1) is a proinflammatory involved in many inflammatory diseases. However, its roles in intracerebral hemorrhage (ICH) remain unknown. The purpose of this study was to examine the correlation between changes in serum levels of HMGB1 following acute ICH and the severity of stroke as well as the underlying mechanism. Changes in serum levels of HMGB1 in 60 consecutive patients with primary hemispheric ICH within 12 hours of onset of symptoms were determined. The correlation of HMGB1 with disease severity, IL-6, and TNF-α was analyzed. Changes in HMGB1 levels were detected with ELISA and Western blot. Compared with normal controls, patients with ICH had markedly elevated levels of HMGB1, which was significantly correlated with the levels of IL-6 and TNF-α, NIHSS score at the 10th day, and mRS score at 3 months. In comparison with the control group, the levels of HMGB1 in the perihematomal tissue in mice with ICH increased dramatically, peaked at 72 hours, and decreased at 5 days. Meanwhile, heme could stimulate cultured microglia to release large amounts of HMGB1 whereasFe 2 + / 3 + ions failed to stimulate HMGB1 production from microglia. Our findings suggest that HMGB1 may play an essential role in the ICH-caused inflammatory injury.